Kovner vs. Kovner: “A Parting from the South” vs. “Combat Page” - Shoham, Reʾuven (AJS review, 1997)
The poet Abba Kovner was a partisan and freedom fighter during World War II (1942-1945), made aliyah in 1945, and published his first long poem, ‘Ad lo ’or (“Until There Was No Light”), in 1947. At the outbreak of the Israeli War of Independence he fought on the Egyptian front (1947-48), serving as a cultural officer, or politruk in the Giv'ati Brigade. Preda me-ha-darom (“A Parting from the South”), his second long poem and one of the pivotal works by a modern Hebrew poet, was written against the background of the War of Independence. However, critics have not yet been able to find a fitting place for it in the canon of Hebrew poetry and culture, although several serious attempts have been made. The present study does not refer to every aspect of this complex poem but focuses on one particular point. I contend that “A Parting from the South” implies an attempt by the visionary speaker of the poem to compel the young country, soon after the war, to part from the world of death, from cultic memories of the dead and guilt feelings toward them (the dead in the 1948 war in Israel and the dead in the ghettos of Nazi Europe in World War II). Abba Kovner tries to detach himself, and his readers, from death, to liberate them from the old perspectives.